2019
DOI: 10.1186/s40494-019-0285-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping diagenesis in archaeological human bones

Abstract: We describe a procedure for ascertaining the extent of diagenesis in archaeological human skeletons through the distribution of Sr, Ba, Cu, Pb, Fe, and Mn in cross-sections of femoral cortical bone. Element mapping is performed through Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS). Absolute calibrations of element concentrations were obtained using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) on adjacent dissolved bulk bone samples. By comparing a modern individual to five me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 94 publications
(120 reference statements)
5
40
2
2
Order By: Relevance
“…The distribution of the Dominican Friary sample, which contained many churchmen, is different from those consisting of skeletons from other contexts Fig. 8 Concentrations of Sr and Ba in femoral cortical bone (µg g −1 ) from early to late Ribe Cathedral graveyard skeletons: AD 800-1050 (a), AD 1225-1425 (b), AD 1425-1738 (c), and AD 1738-1805 (d) somewhat higher than those reported for presentday populations [24,61,64] (Fig. 2), but they were not above the upper bounds of ranges for modern non-buried bones, except for Ribe.…”
Section: Diagenesis Indicators-fe Mn Al Asmentioning
confidence: 84%
See 4 more Smart Citations
“…The distribution of the Dominican Friary sample, which contained many churchmen, is different from those consisting of skeletons from other contexts Fig. 8 Concentrations of Sr and Ba in femoral cortical bone (µg g −1 ) from early to late Ribe Cathedral graveyard skeletons: AD 800-1050 (a), AD 1225-1425 (b), AD 1425-1738 (c), and AD 1738-1805 (d) somewhat higher than those reported for presentday populations [24,61,64] (Fig. 2), but they were not above the upper bounds of ranges for modern non-buried bones, except for Ribe.…”
Section: Diagenesis Indicators-fe Mn Al Asmentioning
confidence: 84%
“…Only cortical bone deeper than 1 mm was used for chemical analyses. Examinations of cortical bone cross-sections have shown that 1 mm is at least twice the depth of physically and chemically degraded bone normally seen in Danish medieval skeletons [24].…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations